1992
DOI: 10.1002/ejsp.2420220304
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive models of stereotype change: (2) Perceptions of homogeneous and heterogeneous groups

Abstract: The reported study compared

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 13 publications
3
52
1
Order By: Relevance
“…Although these were the British Conservative Party in Studies 1 and 2, and a rowing club from a conservative student association in Study 3, they all arguably represent somewhat homogeneous and clearly defined groups, as conservatives tend to be seen. Research has shown that stereotypes change more rapidly in the case of disconfirming evidence stemming from homogeneous groups as opposed to heterogeneous groups (Hewstone et al, 1992b). Future research could therefore include the perceived homogeneity of groups as an important factor influencing the ease with which single outgroup transgressions influence the outgroup stereotype.…”
Section: Discussionmentioning
confidence: 98%
“…Although these were the British Conservative Party in Studies 1 and 2, and a rowing club from a conservative student association in Study 3, they all arguably represent somewhat homogeneous and clearly defined groups, as conservatives tend to be seen. Research has shown that stereotypes change more rapidly in the case of disconfirming evidence stemming from homogeneous groups as opposed to heterogeneous groups (Hewstone et al, 1992b). Future research could therefore include the perceived homogeneity of groups as an important factor influencing the ease with which single outgroup transgressions influence the outgroup stereotype.…”
Section: Discussionmentioning
confidence: 98%
“…Previous work on this issue has yielded inconsistent results. Some (e.g., Rehder & Hastie, 1996;Silka, 1981) have shown that, category homogeneity facilitates changes in beliefs about category characteristics following exposure to discrepant category information, whilst others have shown the opposite effect (Hewstone et al 1992). One explanation for this discrepancy is that the effects of variability depend on the temporal framing of the initial and discrepant category information.…”
Section: Discussionmentioning
confidence: 99%
“…Studies across the two kinds of temporal construal have operationalised variability in different ways, used different kinds disconfirming information and measures of belief change (cf. Hewstone et al, 1992;Rehder & Hastie, 1996). It is possible that these differences in stimulus structure, rather than temporal construal underlie the discrepant findings.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations